Pengaruh Lokasi Terhadap Keputusan Menjadi Nasabah di Bank BSI KCP Pasar Aur Bukittinggi - Dzakiyah Suci Yuhary; Sandra Dewi (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This research is motivated by competition in the banking world. Where Sharia banks are required to be able to influence society with their advantages. With the support of this strategic business location, consumers can make more decisions to become customers at BSI KCP Pasar Aur Bukittinggi. The aim of this research is to find out how much influence location has on the decision to become a customer at BSI KCP Pasar Aur Bukittinggi. This research uses quantitative methods. The data collection technique uses a questionnaire. Sampling in this study used Rao Purba with a sample size of 96 people. The tests used include, Descriptive Analysis, Pre-Research Test (Validity Test and Reliability Test), Classic Assumption Test (Normality Test, Multicollinearity Test and Heteroscedasticity Test), Simple Linear Regression Analysis Test, and Hypothesis Test (t-Test, F Test and R2 test) assisted with SPSS 20. The results of this research partially show that location has a significant influence on customer decisions with a calculated value of tcount ≥ ttable (8.307 ≥ 3.380). Based on the results of research tests using simple linear regression analysis techniques, it can be stated simultaneously or together that there is a positive and significant influence with a significant F value of 0.000 ≤ 0.05. The test value of the coefficient of determination (R2) has an influence of 0.423 or 42.3% on customer decisions, while the remaining 57.7% is influenced or explained by other variables not discussed in this research.